Fast track land reform programme and women in Goromonzi district, Zimbabwe - Chakona, Loveness (Rhodes University, Faculty of Humanities, Department of Sociology, 2012)
From the year 2000, land became the key signifier for tackling the unfinished business of the decolonisation process in Zimbabwe, notably by rectifying the racially-based land injustices of the past through land redistribution. This took the form of the Fast Track Land Reform Programme (FTLRP). However, the racialised character and focus of the FTLRP tended to mask or at least downplay important gender dimensions to land in Zimbabwe. Colonial and post-colonial Zimbabwe (up to 2000) had instigated, propagated and reproduced land ownership, control and access along a distinctively patriarchal basis which left women either totally excluded or incorporated in an oppressive manner. This patriarchal structuring of the land question was rooted in institutions, practices and discourses. Although a burgeoning number of studies have been undertaken on the FTLRP, few have had a distinctively gender focus in seeking to identify, examine and assess the effect of the programme on patriarchal relations and the socio-economic livelihoods of rural women. This thesis makes a contribution to filling this lacuna by offering an empirically-rich study of land redistribution in one particular district in Zimbabwe, namely, Goromonzi District. This entails a focus on women on A1 resettlement farms in the district (and specifically women who came from nearby customary areas) and on women who continue to live in customary areas in the district. My thesis concludes that the FTLRP is seriously flawed in terms of addressing and tackling the patriarchal structures that underpin the Zimbabwean land question.
Keywords: Land reform -- Research -- Zimbabwe; Land settlement -- Government policy -- Zimbabwe; Land reform beneficiaries -- Zimbabwe; Sex discrimination against women -- Zimbabwe; Women's rights -- Zimbabwe